N-Acetylcysteine for Preventing Acetaminophen-Induced Liver Injury: A Comprehensive Review - Licata, Anna; Minissale, Maria Giovanna; Stankevičiūtė, Simona; Sanabria-Cabrera, Judith; Lucena, Maria Isabel; Andrade, Raul J; Almasio, Piero Luigi (Frontiers in Pharmacology, 2022)
AIMS: N-acetylcysteine (NAC) is used as antidote in acetaminophen (APAP) overdose to prevent and mitigate drug-induced liver injury (DILI). Our objective was to review systematically evidences of use of NAC as a therapeutic option for APAP overdose and APAP-related DILI, to define the optimal treatment schedule and timing to start treatment. METHODS: Bibliographic databases (Pubmed, Web of Science, Embase, and MEDLINE) were searched for retrospective, prospective cohort studies, case series and clinical trials. The pre-specified primary outcomes were DILI-related mortality, hepatotoxicity and adverse events (AEs). RESULTS: 34 studies of NAC usage in APAP-DILI cases with 19,580 patients were identified, of whom 2,376 patients developed hepatotoxicity. Mortality rate across different studies ranged from 0 to 53%. Large variability of NAC regimens was found, i.e., intravenously (I.V.) (100 to 150 mg/kg) and orally (70 to 140 mg/kg); and length of treatment varied from 12, 24 or 48 hours for I.V. regimen, and 72 hours for oral administration. Timing of initiation of NAC treatment showed different results in terms of occurrence of hepatotoxicity and mortality: if started within 8 hours and no more than 24 hours from APAP overdose, either intravenously or orally, NAC administration was efficacious in terms of mortality. Most frequent AEs reported were anaphylactic reactions, followed by cutaneous for the IV route and intestinal for the oral one. CONCLUSION: NAC improves hepatotoxicity and reduces mortality. Timing of treatment, ranging from 8 to 24 hours from APAP overdose, regardless of the regimen or route of administration, it is important to prevent or minimize liver damage, particularly in elderly, children, and obese patients